Circulation of individual and collective theoretical supervisory methods in educational supervisory work - Al-Bakri, Ibtihaj Abdulhakam (Journal of Educational and Psychological Sciences, 2023)
This study aimed to review the educational literature of individual and group theoretical supervisory techniques, demonstrate the importance of using these supervisory techniques in the supervisory system in Palestine by using the synthetic analytical approach.The study clarified the role of the supervisor, who represents an important position in educational systems, as he is an expert and specialist in modern curricula and teaching methods. He must develop and improve the educational process by assisting teachers and directing them toward techniques that increase their effectiveness, to accomplish achievements through individual and group theoretical supervisory techniques. The study showed that the task of supervision does not fall on the responsibility of the educational supervisor alone, but rather the supervisory responsibility is shared by the school principal, who is considered a resident educational supervisor. The study concluded with a set of recommendations for educational supervisors, officials, and decision-makers that contribute to improving and developing theoretical supervisory techniques.
Keywords: Supervisory Techniques; Directed Readings; Supervisory Brochure; Operational Research; Educational Seminar